2018
DOI: 10.1007/s00442-018-4127-1
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity may help lizards cope with increasingly variable temperatures

Abstract: Temperature variability is predicted to increase in the coming century due to climate change. However, the biological impact of increased temperature variability on animals remains largely unexplored. Here, we experimentally exposed gravid viviparous lizards (Eremias multiocellata) to two thermal environments [constant daily maximum (CDM) versus variable daily maximum (VDM) treatment with the same average temperature] to address maternal and offspring responses to increased variability in ambient temperature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Given the thermal dependence of food intake and energy budget in animals (Brown et al., 2004; Du et al., 2000; Speakman, 2005), mothers may be able to ‘programme’ the food assimilation efficiency and metabolic capacity of offspring to increase energy income and therefore the threshold of energy limitation under climate warming. For example, females exposed to increasing or highly variable temperatures produce offspring with higher metabolic rates and higher growth rates in marine sticklebacks and our study species E. multiocellata (Ma et al., 2018; Shama et al., 2014).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Given the thermal dependence of food intake and energy budget in animals (Brown et al., 2004; Du et al., 2000; Speakman, 2005), mothers may be able to ‘programme’ the food assimilation efficiency and metabolic capacity of offspring to increase energy income and therefore the threshold of energy limitation under climate warming. For example, females exposed to increasing or highly variable temperatures produce offspring with higher metabolic rates and higher growth rates in marine sticklebacks and our study species E. multiocellata (Ma et al., 2018; Shama et al., 2014).…”
Section: Discussionmentioning
confidence: 86%
“…First, maternal behavioural thermoregulation plays an important role in responding to temperature variation or climate warming in ectothermic animals because effective thermoregulators may buffer the impact of extreme temperatures behaviourally, and thereby have time for intra‐ and inter‐generation plasticity and evolutionary adaptation before they become extinct (Huey et al., 2012; Kearney et al., 2009; Ladyman et al., 2003). For example, maternal behavioural thermoregulation may enable females to manipulate developmental temperatures of embryos that profoundly affect the preferred body temperature, metabolic rate, and probably growth of offspring in E. multiocellata and other lizards (Ma et al., 2018; Paranjpe et al., 2013). Second, maternal effect may mediate oxidative stress, a potentially widespread mechanism underlying life‐history trade‐offs, to shape offspring growth and survival (Monaghan et al., 2009; Vitikainen et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To eliminate the effects of circadian rhythms on metabolic rates, all the trials were conducted between 10:00 AM to 6:00 PM. To minimize the effects of food digestion on metabolic rates, we removed the food and enabled the lizards to fast for at least 12 h prior to the trials started (Ma et al, 2018; Sun, Ma, et al, 2018). Oxygen consumption and carbon dioxide production were used for metabolic rate calculation.…”
Section: Methodsmentioning
confidence: 99%
“…Empirical studies have demonstrated that experimental warming can increase reproductive frequency in oviparous squamates for 2–3 clutches (Du et al 2005b, Lu et al 2018), which also appear in some sites according to our prediction. However, reproductive frequency in viviparous species has not been shown to increase under experimental warming (Ma et al 2018b), although some viviparous species (not including Sceloporus lizards) in warmer regions tend to have a larger probability of producing two litters (or more in very few cases) rather than one per year (Mesquita et al 2016a, Schwarzkopf et al 2016). Under climate change, the reproductive frequency of viviparous species will increase at few sites (4.49% sites) only, where gravid females were estimated to not reproduce every year in recent climates (Fig.…”
Section: Discussionmentioning
confidence: 99%